Cyclicality of International Reserves, Exchange Rate Flexibility, and Output Volatility - Eiji Fujii; Xingwang Qian (CESifo GmbH, 2025)
This paper investigates the cyclicality of international reserves and their role in macroeconomic stabilization. We challenge two widely held assumptions: (1) central banks typically manage IR counter-cyclically—accumulating reserves during booms and drawing them down during downturns; and (2) such interventionist management is primarily associated with rigid exchange rate regimes. Analyzing data from 179 countries (1972-2022), we find that counter-cyclical IR management is less common than often assumed. However, as a macroprudential policy, counter-cyclical international reserves significantly reduce output volatility, particularly when interacting with de facto flexible exchange rate regimes. This stabilizing effect is especially pronounced in emerging markets between the 1997 Asian financial crisis and the 2008 global financial crisis.
Keywords: F34; F31; 330; international reserves; cyclicality; exchange rate regime; macroprudential policy; output volatility.